Can Manganese Dioxide Microspheres be Used as Intermediaries to Alleviate Intervertebral Disc Degeneration With Strengthening Drugs? - Zhang, Wentao; Yang, Ming; Sun, Tianze; Zhang, Jing; Zhao, Yantao; Li, Jingmin; Li, Zhonghai (Frontiers in Bioengineering and Biotechnology, 2022)
Degenerative disc disease (DDD) is a pathological condition associated with intervertebral discs (IVDs) that causes chronic back pain. IVD degeneration has become a significant issue in contemporary society. To date, numerous biological therapies have been applied to alleviate the progression of DDD, among which therapeutic protein injection is the most direct and convenient. However, there are some limitations to applying direct protein injection therapy, the most significant being that the efficacy of this method has a short duration, which is a major factor in its effectiveness and the resulting patient satisfaction. How do we solve this problem? Or how can the effectiveness of the treatment be enhanced? It has been proved that manganese dioxide (MnO2) microspheres, widely used in environmental science, not only regulate the expression of cell genes and cytokines in the microenvironment, but also have the ability to release drugs slowly. We propose that direct injection of protein encapsulated in hollow MnO2 (h-MnO2) microspheres could solve the problem of rapid drug release. In addition, the use of a MnO2 and protein injection in the treatment of DDD may have a synergistic effect, which would be highly significant for the degradation of pro-inflammatory factors in the DDD microenvironment. Therefore, the combination of MnO2 and protein may provide a new therapeutic approach to alleviate the progression of DDD.